A combination of 1064 nm Q‐switched fractional ND‐YAG laser with a nonfractional microsecond pulsed technology has a synergistic effect for nonablative facial rejuvenation. (1st January 2021) - Akerman, Lehavit; Lapidoth, Moshe; Levi, Assi; Sharon, Eran; Hilewitz, Daniel; Solomon‐Cohen, Efrat
Abstract: Background: Non‐ablative fractionated lasers for facial rejuvenation are increasingly preferred over ablative lasers due to their minimal downtime and fewer adverse events. The synergistic effect of the Q‐switched fractional (QSF) 1064‐nm neodymium‐doped yttrium aluminum garnet (Nd:YAG) laser, in combination with the non‐fractional microsecond pulsed technology has yet to be fully evaluated. Aim: Our objective was to determine the safety and efficacy of this combination treatment for skin rejuvenation. Methods: Patients who underwent treatment using the QSF‐Nd:YAG laser, followed by the non‐fractional microsecond pulsed Nd:YAG were evaluated retrospectively using a novel 3D imaging modality for degree of facial erythema, wrinkles surface area, and wrinkle depth. Pain perception, adverse effects, and patient satisfaction were assessed at the 2‐month post‐treatment follow‐up visit, graded on a scale of 1‐ 5 (1 = not satisfied, 5 = very satisfied). Results: Ten female patients' ages 44‐67 (mean 55 years) completed both treatment and follow‐up period, with an overall mild improvement in facial erythema and wrinkle surface area (mean improvement of 18% and 19.5% accordingly), as well as a mild improvement in overall wrinkle depth. Pain and adverse effects were mild and transient. Patients' satisfaction was high. Conclusion: The combination of the QSF‐Nd:YAG laser and non‐fractional microsecond pulsed technology, using a single Nd:YAG 1064 nm laser platform, was found safe and effective as a non‐ablative modality for facial rejuvenation, as demonstrated by a novel 3D imaging modality.